1986
DOI: 10.1177/019874298601100308
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and Student Ratings of the Disturbingness of Common Problem Behaviors

Abstract: Responses by 43 teachers and 200 junior high school students to the 55 common problem behaviors listed on the Disturbing Behavior Checklist I are compared. Rank orderings of the two groups' ratings of the disturbingness of behaviors show moderate agreement. Both teachers and students rated several of the same acting-out, aggressive behaviors as the most disturbing to them, although overall teachers rated the behaviors as more disturbing than did students. Behaviors for which there exist the widest discrepancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The implications of these findings are that girls' lower tolerance of aggression and greater willingness to interact may result in both greater sensitivity to deviance and a willingness to assist others to develop appropriate social skills. Also analyzing disturbingness ratings, Mullen and Wood (1986) found that students were most bothered by social defiance, but were less disturbed by all behaviors than were teachers. Students nonetheless disapproved of the same behaviors that teachers did.…”
Section: Problemsmentioning
confidence: 99%
See 4 more Smart Citations
“…The implications of these findings are that girls' lower tolerance of aggression and greater willingness to interact may result in both greater sensitivity to deviance and a willingness to assist others to develop appropriate social skills. Also analyzing disturbingness ratings, Mullen and Wood (1986) found that students were most bothered by social defiance, but were less disturbed by all behaviors than were teachers. Students nonetheless disapproved of the same behaviors that teachers did.…”
Section: Problemsmentioning
confidence: 99%
“…In addition, youngsters are more accepting as they mature into middle childhood, generally agree with teachers on which behaviors are unacceptable, cite external causes for problem behaviors, and report frequent bullying by peers and poor handling by school personnel (Guttmann, 1982;Hazier et a l , 1991;Mullen & Wood, 1986; J. S. Safran & S. P. Safran, 1985;S. P. Safran et al, 1994;Vidoni et al, 1983).…”
Section: Problemsmentioning
confidence: 99%
See 3 more Smart Citations